Febrile ulceronecrotic Mucha–Habermann disease after levamisole‐adulterated cocaine use: an unusual case. (1st October 2018) - Fongue, J.; Amatore, F.; Benzaquen, M.; Spadari, M.; Granel, B.; Berbis, P.
Abstract: Click here for the corresponding questions to this CME article.